2004
DOI: 10.1203/01.pdr.0000100902.76021.8e
|View full text |Cite
|
Sign up to set email alerts
|

Meconium Is a Potent Activator of Complement in Human Serum and in Piglets

Abstract: Meconium aspiration syndrome (MAS) is a clinical condition in the newborn infant with a significant morbidity and mortality. The complex pathophysiology of MAS, leading to both pulmonary and systemic complications, is characterized by an incompletely understood inflammatory reaction. Treatment is symptomatic, mainly limited to airway cleaning and ventilatory support. In this study, we show for the first time that meconium is a potent activator of complement, a key mediator of inflammation. In vitro, meconium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
4
32
0
Order By: Relevance
“…Jones et al 4 demonstrated increased production of inflammatory cytokines in preterm infants with MAS. Castelheim 10 showed compliment activation in human monocytes culture of MAS model.…”
Section: Human Studiesmentioning
confidence: 95%
See 3 more Smart Citations
“…Jones et al 4 demonstrated increased production of inflammatory cytokines in preterm infants with MAS. Castelheim 10 showed compliment activation in human monocytes culture of MAS model.…”
Section: Human Studiesmentioning
confidence: 95%
“…17 Now we describe the pathways of induction of inflammatory response following cell influx. 4 Preterm and term newborns Production of TNFa, IL1b, and IL8 is regulated by IL-10; IL-10 not detected in preterm infants with or without MAS de Beaufort et al 8 Newborn infants Overexpression of IL-8 in MAS in vitro; increased migration of neotrophils; anti-IL-8 antibodies inhibit neutrophil migration Uotila and Kaapa 9 Human monocytes In culture increase of cycloxygenase-2 expression in vitro Castellheim et al 10 Human monocytes in culture Complement activation in MAS Animal models of MAS Tyler et al 3 Animal models Surfactant inactivation, chemical pneumonitis, airway obstruction, direct toxic damage of animal lung tissues Zagariya et al 6 Rabbit pups Intense inflammatory reactions involved in meconium-induced injury in vivo; expression of endothelin 1 in MAS Davey et al 11 Piglets Acute decrease in gas exchange and dynamic lung compliance; increase of total lung protein; inhibition of surfactant Holopainen et al 12 Piglets Inflammation, airway epithelium targeted, necrotic changes, phospholipase 2 activity increased. Mollnes et al 13 Animal models Complement activation in MAS Khan et al 14 Mice Increase of IL-13 expression in MAS in vivo; lymphocytic and eosinophilic inflammation Zagariya et al 15 Rabbit pups Phospholipase A2 activates apoptosis, influx of T-lymphocytes and macrophages in vivo; increase of TNFa, IL-1b, IL-6 and IL-8 in MAS in vivo Zagariya et al 16 Rabbit pups Cell death by apoptosis, influx of neutrophils and macrophages in vivo Tessler et al 17 Newborn infants Reactive oxygen species in vitro…”
Section: Inflammatory Responses To Meconiummentioning
confidence: 99%
See 2 more Smart Citations
“…36 Adding meconium to human umbilical serum induced a substantial increase in TCC formation, which was found to be mediated mainly through the alternative activation pathway. As judged by their relative amounts in whole meconium, the lipid and water fractions contributed equally to this activation.…”
Section: Mas and The Complement Systemmentioning
confidence: 97%